Oro Snacks (4Bites) / Muhammad Nur Aiman Khairudzaman ... [et al.] - Muhammad Nur Aiman, Khairudzaman; Nur Sabrina, Fazli; Nur Hidayu, Zahari; Nur Nisyyah, Jafri (2020)
The purpose of why we prepared the business plan is to make sure that our business will run smoothly and will helps us in the future when we want to make any decision making. The business is based on partnership of 4 members which hold an important role such as general manager, administrative manager, marketing manager, operational manager and financial manager.